The nature of hydrothermal fluids associated with granite-hosted, polymetallic mineralisation in the Eastern lobe of the bushveld complex. - Freeman, Lauren Anne (My University, 1998)
Numerous small base-metal deposits occur in the acidic rocks of the Bushveld Complex, and modern exploration programs are currently re-examining this metallotect in an attempt to refine the current working hypothesis for mineralisation in these granites. The hypothesis proposed for the origin of mineralisation is multifaceted, encompassing both spatial and temporal relationships between at least three episodes of ore formation. The first episode of mineralisation (typified by the Zaaiplaats tin deposit) occurred at relatively high temperatures (>600'C to 4000' C), and resulted in the formation of orthomagmatic cassiterite, scheelite and an early generation of fluorite. At lower temperatures (200°C<T<400°C), where processes were essentially fluid dominated, a mesothermal Cu-Pb-Zn-As-Ag-Au assemblage was deposited (exemplified by the Spoedwel, Boschhoek and Albert copper and silver deposits). A third episode of mineralisation resulted in the formation of an Fe-U-F assemblage and is recognised at several, but not necessanly all, of the deposits examined (for example, the Albert silver deposit). The extended nature of this three-stage paragenetic sequence is considered to reflect widespread mixing between an early fluid derived by H20-saturation of the granitic magma and an external meteoric/connate fluid, circulation of which was stimulated by the long-lived high heat-productive capacity of the Bushveld granites, as well as exhumation of the metallotect; The early high-temperature Sn/W assemblage was precipitated while magmatic fluids dominated the system. With time, the pluton cooled and was subject to regional uplift. Fractures developed, acting as conduits for external fluids of meteoric and/or connate origin. The late magmatic fluids, enriched in incompatible metals (and volatiles), interacted with the latter fluid, resulting in the localised precipitation of a secondary, lower-temperature mineral assemblage (Cu-Pb-Zn) in the zone of fluid mixing. As the external fluid component became progressively more dominant, the paragenesis changed, forming the :final Fe-U-F assemblage. The formation of these three different, temporally separate assemblages is adequately explained in terms of a fluid mixing model, wherein the concentration ofmetaIs and localisation of ore deposits are controlled by lithology and structure.
A thesis submitted in fulfilment of the requirements for the degree of PhD in Geology University of the Witwatersrand
Keywords: Granite.; Petrology.; Mineralogy -- Research.; Physical geology.; Igneous rocks.